End of life in COPD patients: time for a change - Braço Forte, C; Sousa, S (My University, 2017)
End-of-life decision-making is as important in COPD as in cancer, and doctor-patient communication is key to it http://ow.ly/NKcX30ghoUi.
Keywords: Doença Pulmonar Obstrutiva Crónica; Cuidados Terminais; Terminal Care; Pulmonary Disease, Chronic Obstructive